Facilitation and Service Delivery in the National Police Service in Nairobi County, Kenya - Nassiuma, Bernard Kibeti; Young Ogola, Humphrey; Mwangi Kung’u, David (Advances in Social Sciences Research Journal, 2021)
Purpose: The purpose of the study was to evaluate the effects of facilitation on service delivery in the National Police Service (NPS), Nairobi County, Kenya. The study was anchored on the New Public Management Theory; it heralds the transformation of citizens into customers of public services who deserve feedback on police service delivery. Methodology: Pragmatic philosophical approach was used to support this study. The qualitative and quantitative methods of inquiry were used to generate evidence to support the evaluation. The target population for the study was 2100 police officers in Nairobi County from which a sample of 215 respondents was selected using simple random sampling techniques. While the members 105 of the public were purposely selected. Questionnaires and key informant interview guides were the main data collection tools used in the study. The qualitative data were thematically analyzed while the quantitative data were analyzed using frequency counts, means, standard deviation, multiple regression, chi-square tests, and Pearson and Spearman rank correlation. Findings: The majority of the respondents in the study were males aged between 26-35 years and over 60% of the respondents were of the opinion that police reforms had increased police mobility. Equally, the majority (64%) indicated that the infrastructure was poor, in addition to poor feedback mechanisms, which affected effective service delivery. Contribution to Theory Practice and Policy: The study points out the key factors which hinder effective service delivery in the Kenya Police service despite the implementation of police service reforms. Key Words: Facilitation, Service Delivery, Police Reforms, National Police Service